Commemorating Canada : history, heritage, and memory, 1850s-1990s - Morgan, Cecilia, 1958- (Themes in Canadian history., 2016)
"Commemorating Canada is a concise narrative overview of the development of history and commemoration in Canada, designed for use in courses on public history, historical memory, heritage preservation, and related areas. Examining why, when, where, and for whom historical narratives have been important, Cecilia Morgan describes the growth of historical pageantry, popular history, textbooks, historical societies, museums, and monuments through the nineteenth and twentieth centuries. Showing how Canadians have clashed over conflicting interpretations of history and how they have come together to create shared histories, she demonstrates the importance of history in shaping Canadian identity. Though public history in both French and English Canada was written predominantly by white, middle-class men, Morgan also discusses the activism and agency of women, immigrants, and Indigenous peoples. The book concludes with a brief examination of present-day debates over Canada's history and Canadians' continuing interest in their pasts."--